Agriculture - Mukherji, Aditi; Arndt, Claudia; Arango, Jacobo; Flintan, Fiona E.; Derera, John; Francesconi, Wendy; Jones, Sarah K.; Loboguerrero Rodriguez, Ana María; Merrey, Douglas J.; Mockshell, Jonathan; Quintero, Marcela; Mulat, Daniel Girma; et al. (International Energy Agency, 2023)
The Breakthrough Agenda was launched by 45 world leaders at COP 26 and is a commitment to work together this decade to accelerate innovation and deployment of clean technologies, making them accessible and affordable for all this decade. To kick-start this Agenda, countries endorsed Breakthrough goals to make clean technologies and sustainable practices more affordable, accessible and attractive than their alternatives by 2030 in the power, road transport, steel, hydrogen and agriculture sectors. This report also covers the buildings and cement sectors, where new breakthroughs are being considered. The Breakthrough Agenda establishes an annual cycle to track developments towards these goals, identify where further co-ordinated international action is urgently needed to accelerate progress and then galvanise public and private international action behind these specific priorities in order to make these transitions quicker, cheaper and easier for all. The 2023 Report includes a chapter written by CGIAR scientists.